Local Government Administration Strategy and Rural Development in Ika North East Local Government Area of Delta State - Victor Efeizomor; Kifordu Anyibuofu Anthony; Broderick Tumbo (CV. Proaksara Global Transeduka, 2025)
Rural transformation is a vital component of sustainable development, with the potential to alleviate poverty, enhance livelihoods, and improve the overall quality of life for rural inhabitants. However, the achievement of rural transformation goals has been hindered by inadequate local government strategies, characterized by ineffective community engagement, insufficient resource allocation, and inadequate human resource development. This has resulted in persistent poverty, poor infrastructure, and limited access to basic services, ultimately affecting the quality of life of rural dwellers. In response, this study investigates the Local Government Administration Strategy and Rural Development in Ika North Local Government Area of Delta State. Three research objectives, questions, and hypotheses were formulated to guide the study. A sample size of 193 was selected from a population of 300 rural dwellers in Ika North East Local Government Area of Delta State. Data was collected using a validated questionnaire instrument and analyzed using frequency distribution tables, percentages, and statistical models, including Pearson Product Moment Correlation Coefficients, ANOVA, and Regression analysis. The findings reveal significant relationships between community engagement, resource allocation, human resource development, and rural transformation. The results indicate that these factors are positively related to rural transformation, suggesting that they contribute to the success of rural transformation initiatives. Therefore, local governments should adopt a comprehensive approach that combines community engagement, resource allocation, and human resource development to achieve successful rural transformation.